UPGRADING OF INDONESIAN LOW RANK COAL BY STEAM DRYING METHOD - Datin Fatia Umar; Bukin Daulay; Hiromoto Usui; Slamet Suprapto (Indonesian Mining Journal, 2005)
Experiments were carried out to produce upgraded coals with low moisture content by steam drying method. An Indonesian low rank coal, Berau coal with moisture content of 16.13% and calorific value of 5324 cal/g in air dried basis (adb) was treated by steam drying at temperature of 225 - 300°C in an autoclave to study process temperature effect. The results of proximate and ultimate analyses show that moisture content decrease by increasing the temperature process. The moisture content reduces to 0.86% and the calorific value increases up to 6760 cal/g in adb when the coal has been treated at the temperature of 300°C. Furthermore, the specific surface area and combustion characteristics of coals were influenced by the upgrading process.